2011
DOI: 10.4284/0038-4038-77.4.914
|View full text |Cite
|
Sign up to set email alerts
|

Do Remittances Induce Inflation? Fresh Evidence from Developing Countries

Abstract: The goal of this article is to examine the determinants of inflation in both the short run and the long run for 54 developing countries using a panel data set covering the 1995-2004 period. Apart from the commonly used economic determinants of inflation, we model the impact of remittances and institutional variables on inflation. Using the Arellano and Bond panel dynamic estimator and the Arellano and Bover and the Blundell and Bond system generalized method of moments estimator, we find evidence that in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 43 publications
(58 reference statements)
9
52
0
10
Order By: Relevance
“…An increase in remittances creates inflationary pressure in our model, as that found by Narayan et al [2], Vacaflores [3], and Mandelman [12]. In terms of the interest rate response, Giuliano and Ruiz-Arranz [30] provide evidence of the beneficial effect that remittances have in alleviating liquidity constraints, and Aggarwal et al [31] show that remittances have a positive impact on financial sector development.…”
Section: Isrn Economicssupporting
confidence: 61%
See 2 more Smart Citations
“…An increase in remittances creates inflationary pressure in our model, as that found by Narayan et al [2], Vacaflores [3], and Mandelman [12]. In terms of the interest rate response, Giuliano and Ruiz-Arranz [30] provide evidence of the beneficial effect that remittances have in alleviating liquidity constraints, and Aggarwal et al [31] show that remittances have a positive impact on financial sector development.…”
Section: Isrn Economicssupporting
confidence: 61%
“…Since remittance inflows generate additional economic activity-as they usually increase domestic consumptionthey are thought to generate inflationary pressures. Narayan et al [2] confirm this effect in a set of 54 developing countries for the period 1995-2004, showing that remittances generate inflationary pressures, which becomes accentuated in the long run. Vacaflores [3] uses quarterly data and also finds that increases in remittances led to increases in inflation for a set of 11 Latin American countries in the last 15 years.…”
Section: Literature Reviewmentioning
confidence: 49%
See 1 more Smart Citation
“… argues that the inflows of remittances can generate inflationary pressure, especially if they stimulate internal demand for imported goods. confirm this effect in a set of 54 developing countries for the period 1995–2004, showing that remittances generate inflationary pressures, which becomes accentuated in the long run. The findings in also imply that remittances give rise to inflation.…”
Section: Literature Reviewmentioning
confidence: 55%
“…Glytsos [60,61] finds that remittances have an asymmetric impact on economic growth. Other studies have examined the impacts of remittances on various factors of growth: Edwards, Ureta [62], Hildebrandt, McKenzie [63], López-Córdova [64], Gitter, Barham [65], Amuedo-Dorantes et al [66], and Acosta et al [67] analysed the impact on human capital; Demirgüç-Kunt et al [68] were concerned with the impact on financial development of increasing resources for health and education; Chami et al [14] and Jackman et al [69] examined the impact on investment volatility; Narayanet al [70] found that remittances lead to inflation; and Pozo [71] investigated the impact on the real exchange rate. Remittances promote economic growth by providing additional foreign exchange and financing business investments [72,73].…”
Section: Literature Reviewmentioning
confidence: 99%